Local Government Readiness for Digital Transformastion Enhancing Fisheries MSMES Performance in Maluku - Christy Clayde Latupeirissa; Paskanova Christi Gainau; Senda Yunita Leatemia (Pattimura University, 2026)
Digital transformation is a fundamental requirement for achieving effective, efficient, and transparent governance. In the local government context, readiness for digital transformation involves more than technological capability; it requires supporting policies, adequate human resources, organizational cultural alignment, and strong leadership commitment. This study analyzes the readiness of local governments to support digital transformation in the fisheries sector in Maluku Province and Ambon City. A descriptive qualitative approach with purposive sampling was used, and data were collected through in-depth interviews with section-head-level officials from five regional agencies. Data were analyzed using the Miles and Huberman framework through data reduction, data display, and conclusion drawing, verified through source triangulation. The findings show that digitalization initiatives remain limited, unstructured, and still at the planning stage, mainly focused on market retribution and fish auction site management to increase local revenue rather than improving public services. There are no specific policies or budget allocations, and fishing communities face limited device access and internet connectivity. Based on the Capability Maturity Model Integration, the digital maturity level is at Level 1 (initial). The study concludes that strategic policies, improved human resource capacity, infrastructure support, and digital literacy are essential to achieve sustainable digital transformation.